Last seen - Ellison, J. T. (Thomas & Mercer, 2025)
Halley James knows her marriage is over. But she's not prepared for the rest of her life to fall apart too ... She just lost her job at the forensics lab. Her dad needs emergency surgery. But the biggest blow comes back home in Marchburg, Virginia, where she discovers her mother didn't actually die in a car crash. Her mom was murdered--and her father lied about it all these years ... Since she was six years old, it's been Halley and her dad. Now, she doesn't know what to believe. Desperate for the truth, Halley chases down a lead in Brockville, Tennessee. But all there is not as it seems. Brockville's utopian charm hides a chilling darkness. And Halley's search for answers threatens to expose an unspeakable reality.